If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 = -3x + 7 Reorder the terms: 2 + 5x = -3x + 7 Reorder the terms: 2 + 5x = 7 + -3x Solving 2 + 5x = 7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 2 + 5x + 3x = 7 + -3x + 3x Combine like terms: 5x + 3x = 8x 2 + 8x = 7 + -3x + 3x Combine like terms: -3x + 3x = 0 2 + 8x = 7 + 0 2 + 8x = 7 Add '-2' to each side of the equation. 2 + -2 + 8x = 7 + -2 Combine like terms: 2 + -2 = 0 0 + 8x = 7 + -2 8x = 7 + -2 Combine like terms: 7 + -2 = 5 8x = 5 Divide each side by '8'. x = 0.625 Simplifying x = 0.625
| 21x+121=-104 | | (X+1)(x-1)+x(x-1)=x^2 | | 4=3x^2-6x | | X^2-34x=78 | | -2p(2-q/2) | | 5x=100/2 | | x^2-4x/x-2=14-9x/x-2 | | 10(x-7)-8(x+3)=30-x | | 4x^5-32x^3=0 | | -4x+11=14 | | x=16*4x | | 75=20x-15y | | 75=20x+15y | | F(x)=cos(8x-1) | | 58=17x-7y | | 58=17x+7y | | x=15-(13-19) | | x=(x+1)*(1-2x) | | x=(2x+1)*2 | | x=(12x-6)/3 | | x=7*(-x+2) | | 3/4*s=-20 | | S3/4=-20 | | x(x+8)=6x+3 | | 5x+4-3x=7x-8+11 | | y-2=1/2(x-(-4)) | | 218-178= | | 6x^3+15X^2+6x=0 | | 46.37*18.48= | | 2xy*x+3y= | | 6(x^2)+6x-44=0 | | 5(2x-6)=2(5-x) |